ranaazad wrote:

A4G wrote:

What is the value of h ?

(1) h^2 = 36

(2) h^2 + 12h = -36

From statement 2,

(h+6)^2 = 0

h+6 = 0

h = -6, that is clearly sufficient. In this case, B is sufficient

But l approached the statement differently,

h (h+12) = -36

Hence, h=-36 or h = -48. Two values for h. Hence insufficient. In this case the answer would be E

l know it's a silly mistake.

Could someone please clarify.

Regards,

Rana Azad

Hi Rana,

h (h+12) = -36 does not mean h =-36 or h=-48..

substitute and check..

h=-36......

h(h+12) = -36

so -36(-36+12) = -36.......... -36+12 = 1.. NO

h (h+12) = -36 does not mean h =-36

IT means the product of h and h+12 is -36...

so if h=-6, h+12 = -6+12 = 6...

and h*(h+12) = -6 * 6 = -36 ... correct..

Always take all to ONE side and solve

l understand now. Thank you very much, sir!